MicroRNA‐132 directs human periodontal ligament‐derived neural crest stem cell neural differentiation. (17th December 2018) - Ng, Tsz Kin; Yang, Qichen; Fortino, Veronica R.; Lai, Nikky Yuk‐Ki; Carballosa, Carlos M.; Greenberg, Jordan M.; Choy, Kwong Wai; Pelaez, Daniel; Pang, Chi Pui; Cheung, Herman S.
Abstract: Neurogenesis is the basis of stem cell tissue engineering and regenerative medicine for central nervous system (CNS) disorders. We have established differentiation protocols to direct human periodontal ligament‐derived stem cells (PDLSCs) into neuronal lineage, and we recently isolated the neural crest subpopulation from PDLSCs, which are pluripotent in nature. Here, we report the neural differentiation potential of these periodontal ligament‐derived neural crest stem cells (NCSCs) as well as its microRNA (miRNA) regulatory mechanism and function in NCSC neural differentiation. NCSCs, treated with basic fibroblast growth factor and epidermal growth factor‐based differentiation medium for 24 days, expressed neuronal and glial markers (βIII‐tubulin, neurofilament, NeuN, neuron‐specific enolase, GFAP, and S100) and exhibited glutamate‐induced calcium responses. The global miRNA expression profiling identified 60 upregulated and 19 downregulated human miRNAs after neural differentiation, and the gene ontology analysis of the miRNA target genes confirmed the neuronal differentiation‐related biological functions. In addition, overexpression of miR‐132 in NCSCs promoted the expression of neuronal markers and downregulated ZEB2 protein expression. Our results suggested that the pluripotent NCSCs from human periodontal ligament can be directed into neural lineage, which demonstrate its potential in tissue engineering and regenerative medicine for CNS disorders.